Prevalence and Correlates of Client-Perpetrated Abuse Among Female Sex Workers in Two Mexico–U.S. Border Cities. (April 2014) - Ulibarri, Monica D.; Strathdee, Steffanie A.; Lozada, Remedios; Magis-Rodriguez, Carlos; Amaro, Hortensia; O'Campo, Patricia; Patterson, Thomas L.
History of abuse has been associated with greater HIV risk among women. This study examined client-perpetrated abuse among female sex workers (FSWs) in two Mexico–U.S. border cities where HIV prevalence is rising. Among 924 FSWs, prevalence of client-perpetrated abuse was 31%. In multivariate logistic regression models, intimate partner violence (IPV), psychological distress, and having drug-using clients were associated with experiencing client-perpetrated abuse. FSWs along the Mexico–U.S. border report frequently experiencing abuse from both clients and intimate partners, which may have serious mental health consequences. Our findings suggest the need for screening and gender-based violence prevention services for Mexican FSWs.